2010
DOI: 10.1182/blood.v116.21.4262.4262
|View full text |Cite
|
Sign up to set email alerts
|

EARLY Detection of Cardiac and Hepatic Iron Overload by T2* Magnetic Resonance in Very Young Patients with Thalassemia Major in Oman

Abstract: 4262 Background: Despite availability of iron chelation, iron-mediated cardiac toxicity remains the leading cause of death in thalassemia major patients. Although serum ferritin is widely used as a measure of iron overload, this has been challenged by recent magnetic resonance imaging (MRI) studies. Magnetic resonance using myocardial T2* is a highly sensitive, non-invasive and reproducible technique for detection of myocardial iron content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…reported that a significant correlation was not found between cardiac T2*MRI and serum ferritin levels. 35,36 In our study, 402 (39%) patients were diagnosed with hearing loss, with most exhibiting high-frequency sensory hearing loss.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…reported that a significant correlation was not found between cardiac T2*MRI and serum ferritin levels. 35,36 In our study, 402 (39%) patients were diagnosed with hearing loss, with most exhibiting high-frequency sensory hearing loss.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies showed a significant association between increasing cardiac T2*MRI and the mean age and a reverse correlation between T2*MRI and increasing age 33,34 . However, Christoforidis and Fragasso's studies reported that a significant correlation was not found between cardiac T2*MRI and serum ferritin levels 35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in concordance with Fragasso et al ,9 who found that serum ferritin was negatively associated with cardiac T2* values. However, other studies37 38 showed no significant correlation between cardiac T2* and serum ferritin.…”
Section: Discussionmentioning
confidence: 86%